THE CRIMINAL LIABILITY OF LEGAL ENTITIES IN BRAZIL IN LIGHT OF THE NEW ANTI-CORRUPTION LAW - Cordeiro Antonietto, Caio Marcelo; de Castro, Rafael Guedes (European Scientific Journal, ESJ, 2015)
The present article focuses on the study of the liability of the legal entity for acts of corruption introduced in the Brazilian system by Law no. 12.846/2013. Meeting internationally agreed commitments, the Brazilian government issued specific legislation against harmful acts to the public administration, including the strict liability of the legal person for acts of corruption committed in their benefit. Thus, in view of the discussion on the criminal liability of legal entities, of the harmfulness of corruption to the economic system and the new Brazilian form of liability, it was intended herein to draw a criticism that may contribute to improving the fight against corruption as well as the liability system of companies in Brazilian law.